Cambodia : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Cambodians have displayed tremendous resilience. The National Strategic Development Plan (NSDP) has been formulated using the comprehensive Rectangular Strategy of the Royal Government of Cambodia and synthesizes the Cambodia Millennium Development Goals (CMDG), the National Poverty Reduction Strategy (NPRS), et cetera It provides the framework for growth, employment, equity, and efficiency to reach CMDGs. It lays out the vision, goals, strategies, and priority actions. Its implementation will be regularly monitored to make annual adjustments. NSDP could be successfully implemented to attain intended goals and reduce poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet